(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the staff of starshyna in Kodak Palanka. While demonstrating the peculiarities of status and course of life of their representatives, the author appeals to continue schentific work and cooperation in creating a united database of Cossack starshyna.